The turtle Trachemys scripta elegans (Testudines, Emydidae) as an invasive species in a polluted stream of southeastern Brazil - Ferronato, Bruno O. (2009)
The north American freshwater turtle Trachemys scripta elegans has been recently reported as an exotic species in several regions of the world. During an investigation on the ecology of the Chelid turtle Phrynops geoffroanus in a Brazilian anthropogenically altered stream, we captured four T. s. elegans (two males and two females) and observed several other individuals basking. Reproduction was recorded for captive individuals. The occurrence of feral T. s. elegans in southeastern Brazil is considered and aspects that could favor the long term persistence of T. s. elegans at the study site are discussed.